Multimodality Monitoring for Cerebral Perfusion Pressure Optimization in Comatose Patients with Intracerebral Hemorrhage - Ko, Sang-Bae (2011)
BACKGROUND AND PURPOSE: Limited data exists to recommend specific cerebral perfusion pressure (CPP) targets in patients with intracerebral hemorrhage (ICH). We sought to determine the feasibility of brain multimodality monitoring (MMM) for optimizing CPP and potentially reducing secondary brain injury after ICH. METHODS: We retrospectively analyzed brain MMM data targeted at perihematomal brain tissue in 18 comatose ICH patients (median monitoring: 164 hours). Physiological measures were averaged over one-hour intervals corresponding to each microdialysis sample. Metabolic crisis (MC) was defined as a lactate/pyruvate ratio (LPR) >40 with a brain glucose concentration <0.7 mmol/L. Brain tissue hypoxia (BTH) was defined as P(bt)O(2) <15 mm Hg. Pressure reactivity index (PRx) and oxygen reactivity index (ORx) were calculated. RESULTS: Median age was 59 years, median GCS score 6, and median ICH volume was 37.5 ml. The risk of BTH, and to a lesser extent MC, increased with lower CPP values. Multivariable analyses showed that CPP <80 mm Hg was associated with a greater risk of BTH (OR 1.5, 95% CI 1.1–2.1, P=0.01) compared to CPP >100 mm Hg as a reference range. Six patients died (33%). Survivors had significantly higher CPP and P(bt)O(2) and lower ICP values starting on post-bleed day 4, whereas LPR and PRx values were lower, indicating preservation of aerobic metabolism and pressure autoregulation. CONCLUSIONS: P(bt)O(2) monitoring can be used to identify CPP targets for optimal brain tissue oxygenation. In patients who do not undergo MMM, maintaining CPP >80 mm Hg may reduce the risk of BTH.